Abstract 260: TCD Bubble test as a Screening tool for detection of Patent Foramen Ovale in Stroke - Danish Ahammed PK; Paul Alapatt; Aiswarya Raj; Ashraf VV; Shafeed Mattummal (Stroke: Vascular and Interventional Neurology)
Introduction Introduction & Objectives: Transcranial Doppler (TCD) ultrasound provides rapid, noninvasive, real‐time measures of cerebrovascular function. Patent Foramen Ovale (PFO) is fourfold more common in Young Stroke Patients <55 years of age, as opposed to age‐matched controls. The PFO test with TCD, often called a “TCD bubble test,” involves the intravenous injection of micro‐bubbles (air mixed with saline), which can be detected by a TCD system in the Middle Cerebral artery (MCA). The TCD Bubble test, hence, can be used as a screening test in the evaluation of Embolic Stroke Of Undetermined Source. Methods A retrospective observational study was carried out at Aster MIMS Hospital, Kozhikode, where 63 patients with Young stroke were evaluated between April 2021 and October 2022. Along with routine stroke workup, including Transthoracic Echocardiography, TCD bubble tests were performed to detect Right to left shunt. Further, Transesophageal Echocardiography was done to look for Patent Foramen Ovale in TCD Bubble test positive patients. Results TCD Bubble test was detected to be positive in 36 patients and negative in 27 patients. Transesophageal Echocardiography performed in TCD Positive patients confirmed PFO in 35 out of 36 patients. Transthoracic echocardiography, however, could detect PFO only in 10 patients. Conclusion TCD Bubble test can be employed as a screening tool in the evaluation of young stroke to detect Patent Foramen Ovale with efficacy similar to TEE.